Construction of a prognostic model for disulfidptosis related ferroptosis genes lung adenocarcinoma and the role of DECR1 in lung adenocarcinoma - Liu, Haoran; Zhang, Ying; Dong, Yuqing; Jiang, Xintong; Xie, Shuyang; Wang, Pingyu (Frontiers in Immunology, 2025)
BackgroundLung adenocarcinoma (LUAD) is one of the common malignant tumors worldwide, and the 5-year survival rate remains unsatisfactory. To investigate the association between disulfidptosis-related ferroptosis genes (DFRGs) and the prognosis of patients with LUAD, establish a risk prognostic model, validate key biomarkers in vitro, and provide references for the prognosis of LUAD patients.MethodsR software was employed to identify DFRGs. Univariate Cox regression and Lasso-Cox regression analyses were combined to construct a risk score prognostic model. The predictive power of the model was evaluated using Kaplan-Meier survival curves, receiver operating characteristic (ROC) curves, and calibration curves. Immune-related functions, tumor mutation burden, and single-cell analyses were performed on the model genes. Finally, in vitro validation of key prognostic markers was conducted via qRT-PCR, wound healing assay, Transwell assay, CCK8 assay, and flow cytometry apoptosis assay.ResultsSix DFRGs were screened through univariate Cox regression and Lasso-Cox regression analyses to construct the prognostic model. The areas under the ROC curve (AUC) for 1, 2, and 3 years in the training set were 0.836, 0.771, and 0.786, respectively. Decision curve analysis (DCA) indicated that the risk score model effectively predicted lung adenocarcinoma prognosis. In vitro validation demonstrated that knockdown of DECR1 significantly suppressed lung adenocarcinoma cell proliferation and migration, and promoted cell apoptosis (P < 0.05).ConclusionThis study established a risk score model based on six DFRGs, which demonstrated favorable prognostic value. DECR1 promotes the progression of LUAD and holds promise as an effective biomarker.